ANALYSIS OF STUDENTS’ DIFFICULTIES IN UNDERSTANDING ENGLISH VIDEO (A DESCRIPTIVE STUDY) - Prayudha.S, Joko; Suja, Aidillah (Borneo Journal of English Language Education, 2023)
At this time the use of English has become part of modern human communication habits. Almost all existing linguistic aspects also often switch in English as a variation of language use. Even so, the use and understanding of good and correct English is still very necessary to be taught to students so that they have a good understanding of the use of English. One way to practice English comprehension is through the use of English videos. Videos in English provide opportunities for students to understand more broadly how the language is used in everyday life. However, in fact there are still many students who still have difficulty understanding the meaning and use of English sentences when watching English videos. Therefore this study examines students' perceptions of difficulties in understanding the meaning and use of English when watching English videos. The research method used is qualitative through a descriptive approach. The informants in this study consisted of several students who attended English classes by watching English videos. Data obtained through learning observation and interviews. Data were analyzed through data reduction, data display, and conclusions. The results of the study showed that students experienced various difficulties when understanding words or sentences from the English videos they watched, such as the use of foreign vocabulary that they had not encountered before, fast dialogue which made it difficult for students to digest the intent of the video conversation, students experienced obstacles in constructing meaning. and descriptions of scenes making it difficult to understand the context of sentences, lack of understanding of students in connecting vocabulary into an ambiguous sentence, and limitations of students in exploring the storyline of the video shown. To overcome this difficulty problem, English teachers need to provide appropriate teaching solutions so that students can better understand the meaning of English video dialogue so that they can build skills in constructing good and correct student sentence patterns.